PENGARUH KUALITAS LAYANAN, KEPUASAN, DAN KEPERCAYAAN PADA PENGGUNAAN APLIKASI MOBILE BANKING TERHADAP MAHASISWA SEBAGAI NASABAH BANK SYARIAH DI UNIVERSITAS YUDHARTA PASURUAN - Abdillah Mundir; Muhammad Nizar; Dewi Rosyiqoh Athiroh (JPSDa: Jurnal Perbankan Syariah Darussalam, 2022)
This research is motivated by the existence of Islamic mobile banking at the University of Yudharta Pasuruan students. This study aims to determine how the quality of service, satisfaction, trust and customer loyalty to Islamic mobile banking. This research is a type of quantitative research using a descriptive approach. The data collection technique is using questionnaires or questionnaires distributed to students at the University of Yudharta Pasuruan who use mobile banking. The object of this research is 106 people. The data analysis technique used to test the hypothesis in this research is multiple linear regression analysis. Based on the results of the study, it was found that: service quality has a positive effect on the variables of service quality, satisfaction, trust, most of them answered agree, strongly agree and a small part choose less agree. From the results of the research instrument, all items have a correlation index greater than 0.05 and a Cronbach Alpha index of 0.769 (X1), Cronbach Alpha 0.705 (X2), Cronbach Alpha 0.767 (X3) which means that it is reliable in accordance with the provisions of the reliability of the alpha value. Variables of service quality, satisfaction, trust have a positive effect on the loyalty variable, this is indicated by the value of multiple linear regression coefficients of 0.08 (X1), 0.062 (X2), 0.727 (X3) units, this means if there is an increase of one the unit for the Loyalty variable, then the level of service quality satisfaction, trustworthiness is .08 (X1), 0.062 (X2), 0.727 (X3), and vice versa. Based on the t-test, it explains the significant results, between the loyalty variables and the service quality, satisfaction, and trust variables. this is indicated by the value of tcount > ttable. Simultaneously the quality of service and trust have a positive and significant effect shown 0.000 <a 0.05.